Adoption of green technology and its influence on the environmental behavior of students at the National University of Juliaca, 2023 - Arias Escobar, Jesús (2025)
Strengthening the environmental culture in higher education institutions requires understanding the role of green technology in integrating sustainable practices. The objective of this study was to determine the correlation between its adoption and environmental behavior among university students. A correlational design was applied to a probabilistic sample of 340 students, assessed using a dimension-based Likert questionnaire with high internal consistency (α > 0.90). Scores were aggregated into global indices and classified into low, medium, and high levels using statistical cut-off points. Data analysis included descriptive statistics and Spearman’s Rho correlations. Results showed that green technology adoption was mainly concentrated at medium levels (90.3 %). Both variables exhibited a positive and moderate correlation (ρ = 0.301, p < 0.001). Sustainable digital activity showed the strongest association with environmental behavior (ρ = 0.467), followed by energy efficiency (ρ = 0.325), energy saving (ρ = 0.277), and reduction of toxic elements (ρ = 0.257). Academic variables showed no significant relationships. These findings highlight the importance of promoting institutional policies that strengthen the responsible use of green technologies within the university context.